Real-world data to improve organ and tissue donation policies: lessons learned from the tissue and organ donor epidemiology study - Melissa A. Greenwald; Hussein Ezzeldin; Emily A. Blumberg; Barbee I. Whitaker; Richard A. Forshee (BMC, 2024)
Abstract Background The transplantation of human organs, and some human tissues, is often the only life-saving therapy available for serious and life-threatening congenital, inherited or acquired diseases. However, it is associated with a risk of transmission of communicable diseases from donor to recipient. It is imperative to understand the characteristics of the donor population (including both potential and actual donors) to inform policies that protect recipient safety. The Tissue and Organ Donor Epidemiology Study (TODES) was a pilot project designed to identify and collect standardized information on deceased persons referred for organ, tissue and/or eye donation, and to estimate (to the extent possible) infectious disease prevalence and incidence of human immunodeficiency virus (HIV), hepatitis B virus (HBV) and hepatitis C virus (HCV) in this population. TODES is summarized here to shed light on addressable limitations on accessing data needed for transplant recipient safety. Limitations, future research needs and potential pathways to solve the remaining data needs are explored. Methods Retrospective data for all deceased donors during a 5-year period from 2009 to 2013 were obtained from participating organ procurement organizations (OPOs), tissue establishments and eye banks. These decedent data were used to ascertain whether the available real-world data (RWD) could be used to inform donor screening and testing policy. Results The TODES database contains 291 848 records received from nine OPOs and 42 451 records received from four eye banks. Data were analysed from deceased donors with at least one organ, tissue or ocular tissue recovered with the intent to transplant. Results for potential donors were not analysed. Available RWD at the time of the TODES study were not fit-for-purpose to help characterize the organ, tissue and eye donor populations and/or to inform donor screening policy. Conclusions Recent advances in electronic data collection systems make it more realistic to now collect fit-for-purpose RWD that address the research needed to improve transplant safety.